Síndrome 49, XXXXY. A propósito de un caso. - Martínez Basalo, Caridad; Martínez Martínez, Roberto; Ruíz Rizo, Eva; Hernández, Alejandro; Cantú, José María (Revista Cubana de Pediatría, 2023)
Describe hallazgos clínicos, radiográficos y citogenéticos en un caso.